Validity and Reliability of the Seizure Self-Efficacy Scale for Children with Epilepsy - TUTAR GÜVEN, Şerife (Noro Psikiyatr Ars, 2015)
INTRODUCTION: This study aims to adapt the Seizure Self-Efficacy Scale for Children (SSES-C) into Turkish and then assess its validity and reliability in children with epilepsy. METHODS: The study sample consisted of 166 children (aged 9–17 years) with epilepsy who attended of Akdeniz University Hospital, Antalya Training and Research Hospital, and Bursa Dortcelik Children’s Hospital Pediatric Neurology Clinics between July 2012 and March 2013. All research data were collected by a researcher in face-to-face interviews using Child Information Form, Seizure Self-Efficacy Scale for Children and Children’s Depression Scale. The Seizure Self-Efficacy Scale for Children is a 15-item, 5-point Likert scale designed by Caplin et al. (2002). RESULTS: The linguistic adaptation and validation of the scale was conducted by seven experts. To evaluate the content validity of the scale, we elicited judgments from a panel of 10 content experts. The expert judgments showed that the correlation between the items on the scale was fairly good (Kendall’s W=0.411, p<0.001, ki-kare: 57.495). Load factor of 40% and a large factor analysis included analysis of substances and two factors accounting for 49.67% of the total variance explained. We calculated Cronbach’s alpha coefficient for the internal consistency and the full-scale score showed good internal consistency (alpha 0.89). Within the context of reliability studies, it was found correlations varying between 0,98–0,74 for the two sub-factors of the scale. Test/retest correlation coefficients were significant (p<0,01) and high (r=0.99). In parallel forms reliability, the correlations between the Seizure Self-Efficacy Scale for Children and Children’s Depression Rating Scale were found to be negative, moderate and statistically significant (r=−0.58, p<0.001). CONCLUSION: The measurements conducted on the Turkish version of the Seizure Self-Efficacy Scale for Children showed that it is consistent with the original scale, valid and reliable for Turkish society.